Associations between Differentiation in Secondary Science Teaching Activities and Student Motivation to Pursue a Career in a Science Related Field - Waddel, Sandra Dawn (Curtin University, 2017)
Numbers of secondary students, studying science to tertiary level in New Zealand, continues to decrease resulting in a lack of trained scientists to meet demands. This study has researched that a layered curriculum approach to differentiated learning is associated with student motivation to learn science at secondary school and self-selection of science careers. A multi- method approach was taken using a variety of instruments including surveys and interviews for the qualitative data.